A History of Egypt from the End of the Neolithic Period to the Death of Cleopatra VII B.C. 30 (Routledge Revivals) - Budge, E. A. Wallis, author.
1 online resource (260 pages)
Keywords: Sir E. A. Wallis Budge (1857-1934) was Keeper of the British Museum’s department of oriental antiquities from 1894 until his retirement in 1924. Carrying out many missions to Egypt in search of ancient objects, Budge was hugely successful in collecting papyri, statues and other artefacts for the trustees of the British Museum: numbering into the thousands and of great cultural and historical significance. Budge published well over 100 monographs, which shaped the development of future scholarship and are still of great academic value today, dealing with subjects such as Egyptian religion, history and literature. This volume, first published in 1902, is the fourth of eight volumes by Budge dealing with different periods in the history of Egypt. The narrative continues from the end of the reign of Thothmes II to the end of the rule of the XVIIIth Dynasty, 1550-1400 B.C. During these years the Egyptians established their empire in Palestine and Syria and began to consolidate their position on the world stage. This fascinating period is explored by Budge in a classic work of great value to those interested in Egyptology and archaeology.